Amide versus amine ligand paradigm in the direct amination of alcohols with Ru-PNP complexes. Issue 15 (18th July 2018) - Pingen, Dennis; Choi, Jong-Hoo; Allen, Henry; Murray, George; Ganji, Prasad; van Leeuwen, Piet W. N. M.; Prechtl, Martin H. G.; Vogt, Dieter
Abstract : Ruthenium complexes of PNP-ligands bearing secondary amines were found to be inactive in the alcohol amination with NH3, while all complexes of homologous ligands bearing tertiary amines gave active catalysts! Abstract : The catalytic activity of a series of Ru-PNP pincer ligand complexes was studied in the direct amination of alcohols with ammonia. It turned out that all complexes of PNP ligands bearing a secondary amine showed no activity in this hydrogen-shuttling reaction sequence, while all complexes of homologous ligands bearing a tertiary amine gave active catalysts. Further comparative studies on catalysts bearing an acridine-based PNP pincer ligand and a PNP ligand of the Xantphos family provided valuable mechanistic insight that led to the design of a highly active catalyst. It appears that in the group of ligands studied here only ligands that do not form stable Ru-amido complexes are active alcohol amination catalysts.